Cochlear implants – An Overview. Are CIs world’s most successful sensory prostheses? - Dendys, Konrad; Bieniasz, Jan; Bigos, Paula; Kuźnicki, Wojciech; Matkowski, Igor; Potyrała, Piotr (Journal of Education, Health and Sport, 2023)
Cochlear implants (CIs) have greatly improved over the last 2 decades and now are the world’s most successful sensory prostheses, that restored hearing to more than 800,000 deaf people. CIs are small electronic devices that consists of an external portion that is located behind the ear and a second portion that is surgically fixed under the skin, they replace the function of the inner hair cells in the cochlea by direct electrical stimulation of the auditory nerve. Although cochlear implantation has been used for almost 50 years, the indications for this procedure are subject to constant modifications but the main indication is the inability to achieve sufficient speech understanding. Properly implanted, fitted, and rehabilitated hearing prostheses allow to achieve open speech understanding in 70-80% of post-lingual deafness patients and very good speech development results in children. These days cochlear implantation has become the treatment of choice for people with significant hearing loss and are constantly being developed intensively.